Instagram como medio de información para los millennials en la ciudad de Babahoyo - León Cadena, Manuel Antonio (2023)
In these current times, digital platforms are part of society, with the existence of Smartphones and IPhones in conjunction with internet networks, mobile applications that allow access to any type of information and in turn the ease of communicating from anywhere in the world. world. On the other hand, millennials represent the generation that was born between 1982 and 1998, ranging between 18 and 36 years old, representing more than 25% of the world population and 30% of Latin America, and by demographic weight it is a generation hyperconnected with digital technology. The methodology of this case study has a theoretical and descriptive scope that was generated through theoretical foundations of the interrelated variables, for which the inductive-deductive method was applied since all the information was collected from the theoretical bases. In addition, the direct observation method and the survey technique were also used, which allowed the collection of qualitative and quantitative data for the analysis of the information collected. In conclusion, Generation Y or Millennials are attached to changes in technology, so it is necessary to continuously teach them how they can use social networks and how the information system that is shared through these influences. digital platforms, said the case, the information found on Instagram, and thus receive useful content.